Removal of an ectopic canine tooth in the maxillary sinus using bone lid technique - Melisa Ruth; Maria G. Widiastuti; Bambang Dwiraharjo (Journal of Dentomaxillofacial Science, 2022)
Objective: Ectopic teeth are teeth that are located deep in the jawbone or in other areas outside the alveolar bone, such as nasal cavity, chin, mandibular bone, palate, orbital cavity, and maxillary sinus. The presence of teeth in the maxillary sinus can cause an inflammatory reaction in the sinus and cause local sinonasal symptoms such as nasal obstruction, facial fullness, headache, hyposmia, and recurrent chronic sinusitis, due to obstruction of the sinus ostium and it can also develop into cysts. Replantation of bone fragments after tooth extraction using the Bone Lid technique can maintain sinus volume. The aim of this paper is to report the extraction of ectopic teeth in the maxillary sinus by using Bone Lid technique. Methods: A 9-year-old girl was referred from ENT clinic with complaints of pain in the right cheek and sniffles which were diagnosed as maxillary sinusitis. Radiographic examination showed that the canine tooth was located on the right maxillary sinus. The ectopic canine tooth was removed with a modified bone lid technique. Results: The panoramic radiograph and Waters’ projection radiograph postoperatively showed there were no ectopic teeth in the sinus and no volumetric changes of maxillary sinus cavity. In the clinical evaluation of 1 month postoperatively, there were no complaints of pain and sniffles. Conclusion: The use of the Bone Lid technique is beneficial because it maintains sinus volume, thus it does not disturb the function of the maxillary sinus.